Analyzing factors that affect adoption of simple payment services perceived by younger generation in South Korea and exploring how much impact on satisfaction and intention to recommend - OH, Sanggune (KDI School, 2023)
Consumption can be used to explore the index of the degree of the financial system and utilities of consumers in the period. Following the advent of the IT infrastructure, the consumption pattern of the young generation is a rising topic for research and corporations. Because the younger generation, aged 18 to 40, grows up in a technology environment familiar with personalization and convenience based on internet platforms, they are becoming the main consumers. It is imperative to figure out that consumption differences reflect the features of the socio-cultural context and the prospect of the future. Especially South Korea recorded the highest rate of rapid adoption of digital payments. In South Korea, digital payment is formally called ‘Simple Payment Service’ Therefore, how the younger generation who lives in South Korea perceives and understands the characteristics of a simple payment service might be key to increasing its adoption rate. Following on these considerations, this research explore variables that affect adoption, satisfaction and loyalty. The study developed the research questions. i) how factors such as brand image, convenience, customization, cost-benefit, openness, security, and social connectivity affect adoption; ii) how the younger generation’s adoption affects intention to recommend and satisfaction. This study conducted an online survey and got 117 respondents. The researcher calculated the applied factors and executed regression model analysis, ANOVA, and a t-test to check the hypothesis of the raw data. The results of this research found that convenience, security, and social connectivity significantly impact the adoption of the younger generation, while brand image, customization, cost-benefit, and openness impact their inefficient adoption. Plus, Adoption affects satisfaction and intention to recommend efficiently. This research contributed to fostering financial policy implications that promote fostering digital payment services.
Thesis(Master) -- KDI School: Master of Public Policy, 2023
Keywords: Finance--Technological innovations--Korea (South); Financial services industry--Technological innovations--Korea (South)